What's the Point? A Case Study Characterizing Teacher Candidates' Purposes for Practitioner Inquiry. (2nd January 2023) - Rutten, Logan; Wolkenhauer, Rachel
ABSTRACT: Teacher education programs worldwide have adopted the goal of promoting an inquiry stance among teacher candidates. Such programs commonly ground teacher candidates' clinical practice in practitioner inquiry – a cyclical, systematic, and intentional process supported by inquiry communities. While democratic and justice-oriented purposes are theoretically central to the inquiry stance construct, little empirical evidence exists to illustrate how teacher candidates understand their own purposes for inquiring. This article describes the purposes espoused by six teacher candidates as they conducted practitioner inquiry in a clinically rich teacher education program. The teacher candidates exhibited five overlapping purposes for inquiring: process completion purpose, learning purpose, instrumental/efficiency purpose, social change purpose, and responsive purpose. Teacher candidates seldom connected their inquiries to any broader vision of a just, democratic society. While additional research is needed, this study's findings suggest that understanding how teacher candidates understand inquiry's purposes could assist teacher educators in developing teacher candidates' inquiry stances.